Capabilities, Opportunities and Participation : Gender Equality and Development in the Middle East and North Africa Region - Vishwanath, Tara (World Bank, Washington, DC, 2012)
Many countries in the Middle East and North Africa (MENA) region are undergoing a profound transformation. From Bahrain to Yemen, from Tunisia to Egypt, popular movements are calling for political change and a more inclusive development path that will provide ordinary citizens with greater voice, social and economic freedom, and government accountability. Young men and women have been visibly at the forefront of these calls for change, and continue to participate actively. This quick note is based on the overview of the regional report with the same title which complements the 2012 World Development Report (WDR) on gender equality and development. The WDR highlighted the influence and interconnectedness of markets, formal and informal institutions and households in determining gender outcomes. Following the WDR, the report, which will go through a series of consultations in the countries in the region, draws on economic analysis of quantitative data from countries in the region, qualitative research and international evidence. The final report will identify policy directions to better exploit the benefits of a more inclusive development path.